2018
DOI: 10.2147/ott.s137146
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 overexpression protects non-small cell lung cancer cells against osteopontin-induced epithelial-mesenchymal transition by suppressing NF-κB signaling

Abstract: Osteopontin (OPN) is a promoter for tumor progression. It has been reported to promote non-small cell lung cancer (NSCLC) progression via the activation of nuclear factor-κB (NF-κB) signaling. As the increased acetylation of NF-κB p65 is linked to NF-κB activation, the regulation of NF-κB p65 acetylation could be a potential treatment target for OPN-induced NSCLC progression. Sirtuin 1 (SIRT1) is a deacetylase, and the role of SIRT1 in tumor progression is still controversial. The effect and mechanism of SIRT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The analysis of OPN expression levels in 73 advanced NSCLC patients indicated that OPN overexpression was significantly associated with tumor differentiation ( P =0.031), metastasis status ( P =0.019), and the response to platinum-based chemotherapy ( P =0.038). Combined with the reports of Shojaei et al and Li et al, 35 , 36 OPN levels were correlated with the progression of NSCLC and the efficacy of platinum-based chemotherapy in patients with NSCLC. However, the underlying molecular phenomenon is rarely uncovered.…”
Section: Discussionsupporting
confidence: 62%
“…The analysis of OPN expression levels in 73 advanced NSCLC patients indicated that OPN overexpression was significantly associated with tumor differentiation ( P =0.031), metastasis status ( P =0.019), and the response to platinum-based chemotherapy ( P =0.038). Combined with the reports of Shojaei et al and Li et al, 35 , 36 OPN levels were correlated with the progression of NSCLC and the efficacy of platinum-based chemotherapy in patients with NSCLC. However, the underlying molecular phenomenon is rarely uncovered.…”
Section: Discussionsupporting
confidence: 62%
“…SIRT1 plays a crucial role in many pathophysiological processes, including oxidative stress, mitochondria dysfunction and EMT [9,10,13]. We then investigated the involvement of SIRT1 in the protective effect of NaHS on EMT in vivo and in vitro , by examining the SIRT1 levels after CS exposure in the mice and CSE stimulation in the 16HBE cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, SIRT1 can regulate a stress-response transcription factor, FOXO3, thereby downregulating oxidative stress [[10], [11], [12]]. SIRT1 also regulates the RelA/p65 subunit of NF-kB, thereby protecting non-small cell lung cancer cells against osteopontin-induced EMT [13]. Rajendrasozhan and others have shown that SIRT1 is reduced in the lungs of smokers and patients with COPD [14,15], and activation of SIRT1 by SRT1720 protected against CS-induced emphysema in mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that NF-κB plays an important role in the EMT process during liver fibrogenesis 35 and EMT of NSCLC cells occurs via NF-κB activation. 36 Tian et al 37 reported that NF-κB is a master regulator of EMT autocrine loops. We also found that pyrrolidinedithiocarbamate ammonium (PDTC), an inhibitor of NF-κB, could inhibit thrombin-induced increased expression of snail and N-cadherin and inhibit thrombin-induced decreased expression of E-cadherin.…”
Section: Resultsmentioning
confidence: 99%